Ssu72: a versatile protein with functions in transcription and beyond - Fidler, Emma; Dwyer, Katherine; Ansari, Athar (Frontiers in Molecular Biosciences, 2024)
Eukaryotic transcription is a complex process involving a vast network of protein and RNA factors that influence gene expression. The main player in transcription is the RNA polymerase that synthesizes the RNA from the DNA template. RNA polymerase II (RNAPII) transcribes all protein coding genes and some noncoding RNAs in eukaryotic cells. The polymerase is aided by interacting partners that shuttle it along the gene for initiation, elongation and termination of transcription. One of the many factors that assist RNAPII in transcription of genes is Ssu72. It is a carboxy-terminal-domain (CTD)-phosphatase that plays pleiotropic roles in the transcription cycle. It is essential for cell viability in Saccharomyces cerevisiae, the organism in which it was discovered. The homologues of Ssu72 have been identified in humans, mice, plants, flies, and fungi thereby suggesting the evolutionarily conserved nature of the protein. Recent studies have implicated the factor beyond the confines of transcription in homeostasis and diseases.